2011
DOI: 10.1007/s11695-011-0536-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional Importance of Laparoscopic Sleeve Gastrectomy for the Lower Esophageal Sphincter in Patients with Morbid Obesity

Abstract: LSG significantly increased lower esophageal pressure independent of weight loss after LSG and may protect obese patients from gastroesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 36 publications
2
34
3
13
Order By: Relevance
“…Several studies have reported a fall in LESP after LSG [14,19]. However, other studies have stated that LESP remains stable without changing, and some have even reported an increase [20,21]. Petersen reported an increase in sphincter tonus, which was reflected in the manometric measurement of the surgical technique applied independently of weight loss [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a fall in LESP after LSG [14,19]. However, other studies have stated that LESP remains stable without changing, and some have even reported an increase [20,21]. Petersen reported an increase in sphincter tonus, which was reflected in the manometric measurement of the surgical technique applied independently of weight loss [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have stated that LESP remains stable without changing, and some have even reported an increase [20,21]. Petersen reported an increase in sphincter tonus, which was reflected in the manometric measurement of the surgical technique applied independently of weight loss [20]. A loss of sphincter length and the destruction of the angle of His have been considered the most responsible for the decrease in LESP [22].…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed the partial section of the sling fibers of the cardias as cause of these findings. On the contrary, Petersen et al[20] reported an increase in LES pressure regardless of the weight loss, suggesting that this manometric change is related to the position of the stapler in relation to the angle of His. Specifically, the closer the staple line to the gastroesophageal junction, the higher the LES pressure.…”
Section: Gerd and Lsg: The Evidencementioning
confidence: 98%
“…Most studies defined GERD based on proton pump inhibitors (PPIs) use, symptoms evaluation, and presence of esophagitis. Only few studies objectively analyzed patients by esophageal manometry and 24-pH monitoring[15,20,29,33,34,38,40,43,44]. …”
Section: Gerd and Lsg: The Evidencementioning
confidence: 99%
See 1 more Smart Citation